PENGGUNAAN BAHAN ADITIF MASTER GLENIUM ACE 8595 UNTUK MEMINIMALISIR POROSITAS PADA BETON - Fitriani, Amelia Dwi; Mahardana, Zendy Bima; Pasya, Salman Alfaridh; Erwanda, Niko Andika; Fathurrohman, Nadi Rheiza; Qalby, Atsfiela Dzulkhan; Okta, Satria Perdana (Jurnal Riset Rekayasa Sipil, 2024)
Concrete has now become the most essential material in modern construction. The strength and durability of concrete are vital factors that influence the strength and stability of buildings and infrastructure. Porosity refers to the degree to which concrete has voids or voids within its structure. Concrete porosity has a significant impact on concrete compressive strength. The higher the level of porosity, the lower the compressive strength of the concrete. In this research, we conducted a concrete formulation experiment by adding a type F additive to MasterGlenium Ace 8595. This research investigates the effect of adding the additive Master Glenium Ace 8595 on changes in concrete porosity and increasing concrete compressive strength. The results of the research show that from the aggregate suitability testing, it was stated that all the aggregates tested were suitable for use as a building material for concrete, workability testing obtained results with dilute criteria, porosity testing obtained an average porosity of 8.05%, and compressive strength testing obtained an average compressive strength value. -an average of 23.56 MPa indicates an increase of 8.69% of the planned concrete quality. This research concludes that concrete porosity is one of the factors that must be considered to increase the compressive strength of concrete because it significantly influences its density and compressive strength. Keeping the porosity at a low level and the compressive strength of the concrete at a high level can ensure that the concrete structure has good resistance to loads and the environment and reduces the risk of damage and maintenance.